Thinking in education research applying philosophy and theory - Peim, Nick 1952- (London Bloomsbury Academic, 2018)
"Thinking in Education Research examines the resources available from philosophy and theory that can be practically applied to any educational research project. Nick Peim argues that the current well-established divide between theory and the empirical in research methods is unhelpful to students. Instead, Thinking in Education Research looks at major lines of thinking in modern European philosophy, from Kant to Freud and Derrida to Malabou, and how they provide a rich resource for every stage of conducting research. By getting students engaged in 'how to think' and 'how to do', Peim illustrates that thinking is in fact a vital part of how you do research and is not an aside. Essential aspects of the research endeavour are re-examined in the light of key philosophical positions to offer constructive potential, including: defining the object; giving an account of the field; the relation to truth; the process of writing and constructing a case; and the value attributed to formal knowledge. Thinking in Education Research does not try to resolve the unresolved issues of research thinking but rather encourages readers to productively engage with them so that we can enhance the possibilities of research practice and find opportunities for its expansion and refinement. Throughout the chapters, clear and concise summaries of key philosophical positions and ideas are complemented with boxed accounts of how the philosophical debates discussed can be applied to real research projects. These features encourage the reader to consider how they can develop thinking and apply theory at every stage of their own research. This is essential reading for any educational research methods student or practicing researcher for important ways of thinking afresh about research methodology"--Publisher's description.
Dimensions of philosophy -- The elusive object of desire -- The subject -- Truth in question -- Time, place, world -- Data narratives -- New bearings in research thinking.
Includes bibliographical references (pages 264-274) and index.
Keywords: Education -- Research; Education -- Research -- Philosophy; Thought and thinking